First report of maize streak Reunion virus infecting rice in Burkina Faso - (:unkn) unknown (My University, 2024)
To increase our knowledge on viruses infecting rice in Africa, we performed viral metagenomics on rice plants collected in Burkina Faso. Unexpectedly, we identified maize streak Reunion virus (MSRV, Mastrevirus, Geminiviridae) in one rice sample. We also detected MSRV in two wild Poaceae growing within or nearby rice fields. Complete MSRV genomes were obtained and compared with those deposited in public database. We then synthesized and agroinoculated an infectious MSRV clone in two rice species. Moderate symptoms appeared on few rice plants 28 days after inoculation, and the presence of MSRV was confirmed by specific PCR and Sanger sequencing.Although MSRV has so far only been described on maize and wild grasses, our study shows that rice is an alternative host for this virus. While MSRV has been described in African and Asian rice-producing countries, our results are important to consider for epidemiological surveillance of rice fields worldwide.
Keywords: African Research